Sediment deformation and strain evaluation during methane hydrate dissociation in a novel experimental apparatus - Wang, Yi; Kou, Xuan; Feng, Jing-Chun; Li, Xiao-Sen; Zhang, Yu (Applied Energy, 2020)
Natural gas hydrate is an efficient alternative future energy source because huge reserves of methane gas are caged in hydrate-bearing sediments. The research on the deformation of sediments during hydrate dissociation is important for safe hydrate production. In this work, a novel experimental apparatus was designed and built to investigate sediment deformation and strain evaluation during methane hydrate dissociation by depressurization. Experimental results are compared for methane hydrate dissociation for various hydrate saturations, porosities, and particle sizes of sediments. Experimental results illustrate that gas hydrate dissociation by depressurization experienced three main stages. The phenomenon secondary hydrate formation was found during hydrate dissociation by depressurization, which leads to the decrease of sediment permeability. The strain of the sediment is proportional to the volume of methane gas production. Higher hydrate saturation leads to larger sediment deformation by hydrate decomposition. Higher sediment porosity leads to looser sediment particles and larger sediment deformation during hydrate dissociation by depressurization. Larger sediment particle sizes lead to smaller interface areas between hydrate and sediment particles, and larger sediment deformation during hydrate dissociation by depressurization.